The Potential Source of Natural Antioxidant Agent of Cassia alata Microgreen - Rohmanna, Novianti Adi; Mulyawan, Ronny; Majid, Zuliyan Agus Nur Muchlis; Afrina, Dina (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2022)
This study aimed to utilize Cassia alata (C. alata) as a microgreen and evaluate its potential as a source of natural antioxidant agents. The seeds of Cassia alata were cultivated in Rockwool at room temperature (27±1oC). Uppon the appearance of the first true leaves, approximately 21 days after planting, microgreens were harvested from triplicate trays using sterilized scissors. The antioxidant activity was assessed using the DPPH radical scavenging activity method and analyzed via UV-VIS spectrophotometry. The results showed that the IC50 values of C. alata microgreens was 1.789x103 µg/mL, categorizing it as a weak antioxidant. This study indicates that the extract of C. alata microgreens has the potential to be a natural source of antioxidant agents.